Analysis of the Effectiveness of Loyalty Membership Programs in Increasing Customer Retention Using Net Promoter Score (NPS) with Information System Support - Virdies Nur C Cahya; Refius Setyanto; Paradise Paradise (Green Publisher Indonesia, 2025)
This study analyzes the effectiveness of membership loyalty programs in increasing customer retention using Net Promoter Score (NPS) with the support of information systems. Loyalty programs are one of the effective strategies in maintaining long-term relationships with customers. However, its success relies heavily on the right measurement of customer satisfaction, one of which is through NPS. NPS provides clear insights into customer loyalty levels by distinguishing between